The Integration of the Teaching Factory (TEFA) in Fostering an Entrepreneurial Spirit as an Effort to Cultivate a Generation of Job Creators in the Modern Industrial Era - Retmono Agung Winarno (PT FORMOSA CENDEKIA GLOBAL, 2026)
The integration of Teaching Factory (TEFA) in vocational education has become an important strategy in addressing the challenges of the modern industrial era, which requires human resources not only to be job-ready but also capable of creating employment opportunities. The practice-based and industry-oriented TEFA approach is considered effective in fostering students’ entrepreneurial spirit through direct learning experiences in production activities, business management, and marketing. This study aims to analyze the effect of Teaching Factory (TEFA) implementation on the development of entrepreneurial spirit as an effort to create a generation of job creators in the modern industrial era. The study employed a descriptive quantitative approach involving 50 student respondents. Data analysis techniques included descriptive analysis, validity testing, reliability testing, and simple linear regression using SPSS 25.0 for Windows. The results showed that the implementation of TEFA was categorized as high with an average score of 3.94. The activity objectives aspect obtained the highest score of 4.06, while the facilities and infrastructure aspect obtained the lowest score of 3.82. The validity test indicated that all statement items were valid with rcount > rtable (0.361), while the reliability test produced a Cronbach’s Alpha value of 0.815, indicating very high reliability. The simple linear regression analysis showed that TEFA had a significant effect on students’ entrepreneurial spirit with a significance value of 0.012 < 0.05 and a regression coefficient of 0.542. Based on these findings, it can be concluded that the integration of TEFA is able to foster students’ entrepreneurial spirit through industry-based practical learning, thereby having the potential to create a generation of creative, innovative, and adaptive job creators in the modern industrial era.